10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
INTRODUCTION: Recurrent urinary tract infections (rUTIs) impose a significant clinical and economic burden, particularly in women, and contribute to increasing antimicrobial resistance. MV140 is a non-antibiotic sublingual immunostimulatory vaccine developed for the prevention of rUTIs. METHODS: This retrospective 24-month real-world study evaluated 10 women with confirmed rUTIs in the UK, comparing 12-month periods before and after MV140 prophylaxis to assess changes in UTI frequency, antibiotic use, healthcare utilisation, and direct management costs. This study should be considered a preliminary case series given the small sample size. RESULTS: Fifty percent of patients remained UTI-free following MV140 treatment. Mean annual UTI episodes decreased from ⩾3 to 1.9. General practitioner visits declined by approximately 68%, and antibiotic-related costs decreased by 70%. Overall, UTI management costs were reduced by 66% (from ~£394 to £134 per patient), representing a mean saving of £259 (p = 0.0029). No treatment-related adverse events were reported. CONCLUSION: MV140 was associated with reduced recurrence, antibiotic use, and healthcare costs in this real-world cohort. These findings support its potential as a non-antibiotic strategy aligned with antimicrobial stewardship principles. Results should be interpreted as preliminary and hypothesis-generating, requiring validation in larger prospective studies.